2010
DOI: 10.1002/ctpp.201000084
|View full text |Cite
|
Sign up to set email alerts
|

Electron Temperature Dependence of the Dissociative Recombination Coefficient of Molecular Argon Ions Ar+2 with Electrons

Abstract: Key words Stationary afterglow plasma, microwave diagnostics of plasma, electron heating with microwaves, dissociative recombination, electron temperature dependence of recombination, molecular argon ions.A dual mode (T M 010 cylindrical cavity/cylindrical waveguide) microwave apparatus is used to study the ion mobility and dissociative recombination of molecular argon ions with electrons in the afterglow period of a d.c. glow discharge as a function of electron temperature when electrons were heated by microw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
1
6
0
1
Order By: Relevance
“…Our measurements showed that the electron temperature dependence of this coefficient can be described as α(Ar + 2 ) ∼ α 0 (Ar + 2 )T −0.64 e (where α 0 (Ar + 2 ) is the value of the recombination coefficient at 300 K). This dependence is in very good agreement with the earliest experimental results, but not with recent theoretical calculations [8] as summarized in our paper [7]. We have pointed out that there are more recombination channels and the molecular argon ions can be in different vibrational states.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our measurements showed that the electron temperature dependence of this coefficient can be described as α(Ar + 2 ) ∼ α 0 (Ar + 2 )T −0.64 e (where α 0 (Ar + 2 ) is the value of the recombination coefficient at 300 K). This dependence is in very good agreement with the earliest experimental results, but not with recent theoretical calculations [8] as summarized in our paper [7]. We have pointed out that there are more recombination channels and the molecular argon ions can be in different vibrational states.…”
Section: Introductionsupporting
confidence: 91%
“…In our recently published paper [7] we concentrated on the electron temperature dependence of the dissociative recombination coefficient of molecular argon ions Ar + 2 with electrons. Our measurements showed that the electron temperature dependence of this coefficient can be described as α(Ar + 2 ) ∼ α 0 (Ar + 2 )T −0.64 e (where α 0 (Ar + 2 ) is the value of the recombination coefficient at 300 K).…”
Section: Introductionmentioning
confidence: 99%
“…Most Ar + 2 ions have small kinetic energies and only at the lowest pressure a high-component is present. The origin of Ar + 2 ions are gas phase processes, in particular, three-body reactions of Ar + ions with two neutral argon atoms [41][42][43][44][45],…”
Section: Discussionmentioning
confidence: 99%
“…The condition holds for excited Ar * * (4d), Ar * * (6s), and all higher excited levels [41]. Loss of Ar + 2 molecules takes place via electron impact-induced dissociation [41][42][43][44][45][46] Ar…”
Section: Discussionmentioning
confidence: 99%
“…Здесь v и J -колебательное и вращательное квантовые числа иона BA + в начальном электронном состоянии |i . Процесс (1) интенсивно изучался ранее как экспериментально [20][21], так и теоретически [25][26][27][28][29][30][31] для многообразия простых, сложных и кластерных ионов (подробнее см. [17,32,33]).…”
Section: Introductionunclassified